Teaching in times of pandemic, converging towards a hybrid scenario - Nicolas-Sans, Ruben; Bustos Díaz, Javier; Alvarez Valdes, Jesus (Journal of Management and Business Education, 2022)
Hybrid model, online synchronous model, synchronous and blended model: over the last year, teachers have had to adapt to a series of regulatory changes because of the pandemic caused by the SARS-CoV-2 virus, especially in the university environment. In this sense, planning classes has become a suggestion, since in a single semester, different ways of teaching have been employed ranging from 100% synchronous to hybrid. This raises the following question: how have teachers adapted to the changes? Have they changed the way they teach, what are the most commonly used teaching methodologies today? Similarly, has the technological leap been a real problem when changing from the 100% face-to-face model to the different varieties that the health authorities have allowed us to use? For all these reasons, the present study aims to analyze the impact of the application of the different educational models at the university in order to discover the main obstacles teachers have found during this period, and, above all, to study the main methodologies used during this period. To do this, we have carried out a survey among the teachers of the ESIC Business and Marketing School in Barcelona, which has allowed us to collect quantitative and qualitative aspects. As for the conclusions, initially, we can say that there has been a radical change in the way in which classes are being taught. Lectures have almost completely been abandoned and great value is being given to group work and projects. Finally, one of the most outstanding aspects in the conclusions is that teachers emphasize the importance of recycling and methodological innovation in order to continue implementing new teaching methodologies.